2012
DOI: 10.1056/nejmoa1210357
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration in Decompensated Heart Failure with Cardiorenal Syndrome

Abstract: BACKGROUND Ultrafiltration is an alternative strategy to diuretic therapy for the treatment of patients with acute decompensated heart failure. Little is known about the efficacy and safety of ultrafiltration in patients with acute decompensated heart failure complicated by persistent congestion and worsened renal function. METHODS We randomly assigned a total of 188 patients with acute decompensated heart failure, worsened renal function, and persistent congestion to a strategy of stepped pharmacologic ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
609
7
34

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 830 publications
(681 citation statements)
references
References 24 publications
8
609
7
34
Order By: Relevance
“…2 Common to many previous studies in AHF ( 17 and Continuous Ultrafiltration for cOngestive heaRt failurE [CUORE] 18 trials) has been continuous background therapy with high doses of loop diuretics. This class of therapy has intrinsic properties that predispose to WRF by ≥3 mechanisms: direct neurohormonal stimulation, transient depletion of intravascular volume, and frank…”
mentioning
confidence: 99%
“…2 Common to many previous studies in AHF ( 17 and Continuous Ultrafiltration for cOngestive heaRt failurE [CUORE] 18 trials) has been continuous background therapy with high doses of loop diuretics. This class of therapy has intrinsic properties that predispose to WRF by ≥3 mechanisms: direct neurohormonal stimulation, transient depletion of intravascular volume, and frank…”
mentioning
confidence: 99%
“…Even when such concepts have been reflected as part of the inclusion criteria for a clinical trial, all is not as it seems. For example, the inclusion requirements for the Cardiorenal Rescue Study in Acute Decompensated Heart Failure (CARRESS‐HF) required that patients have worsening renal function and persistent oedema, implying that they either had WHF or HF that was failing to respond 25. However, the patients allocated to conventional therapy in the trial subsequently improved, suggesting that they were neither failing to respond nor worsening 25…”
Section: What Is ‘In‐hospital Worsening Heart Failure’ and How Has Thmentioning
confidence: 99%
“…It has been showed that lowering IAB in HF patients improves renal function (20)(21)(22)(23)(24)(25)(26). On the other hand, unlike CARRESS, which was one of the three major studies comparing diuretic treatment with extracorporeal UF in patients with acute decompensated HF, weight loss was similar in both groups while the rate of deterioration in renal function in the extracorporeal UF group was greater than in the UF group (p=0.003) (78).…”
Section: How Does Peritoneal Dialysis Affect Glomerular Filtration Rate?mentioning
confidence: 99%